Improved maritime target tracker using colour fusion - Westall, P.; O'Shea, P.; Ford, J.J.; Hrabar, S. (2009 International Conference on High Performance Computing and Simulation, 2009)
Searching for humans lost in vast stretches of ocean has always been a difficult task. This paper investigates a machine vision system that addresses this problem by exploiting the useful properties of alternate colour spaces. In particular, the paper investigates the fusion of colour information from the HSV, RGB, YCbCr and YIQ colour spaces within the emission matrix of a Hidden Markov Model tracker to enhance video based maritime target detection. The system has shown promising results. The paper also identifies challenges still needing to be met.